Improving intentions to teach in inclusive classrooms: the impact of teacher education courses on future Learning Support Teachers - Paola Aiello; Umesh Sharma (Firenze University Press, 2018)
Educational research is giving much attention to implicit variables such as teachers' attitudes, self-percepts of efficacy, concerns and intentions for the successful implementation of inclusive classroom practices, thus becoming core targets in course programme planning. This study was conducted to assess the possible impact of a teacher education course for future Learning Support Teachers (LSTs) on the variables involved in planning intentional behaviour aimed at fostering school inclusion. Using the Theory of Planned Behaviour as the guiding framework, it was hypothesised that LSTs with lower degree of concerns, higher levels of teaching efficacy, and favourable attitudes are likelier to have positive intentions to implement inclusive practices. Results show that the course may have influenced these variables positively. The authors conclude that further research needs to be conducted on the teaching strategies to be used in these courses. Promuovere l'intenzionalità ad agire in favore dell'inclusione: l'impatto della formazione sugli insegnanti specializzati per il sostegno La ricerca educativa ha già da tempo focalizzato l'attenzione sullo studio delle variabili implicite che influenzano l'agire didattico dei docenti, come gli atteggiamenti, le percezioni di auto-efficacia, le preoccupazioni e le intenzioni ad implementare pratiche didattiche inclusive. In questo filone di ricerche si inserisce il presente studio che ha come obiettivo la valutazione del possibile impatto di un corso di formazione rivolto a futuri insegnanti specializzati per le attività di sostegno sulle variabili che intervengono nella pianificazione di comportamenti intenzionalmente volti a promuovere l'inclusione scolastica. Assumendo la Teoria del Comportamento Pianificato come framework teorico di riferimento, l'ipotesi da cui muove lo studio è che gli insegnanti che mostrano minori preoccupazioni, livelli più elevati di auto-efficacia e atteggiamenti favorevoli, rivelino un'intenzionalità maggiore nell'attuazione di pratiche inclusive. I risultati evidenziano che l'attività di formazione potrebbe aver influenzato positivamente queste variabili, invitando ad ulteriori approfondimenti circa le strategie didattiche da impiegare nei percorsi formativi.